2007
DOI: 10.1073/pnas.0609665104
|View full text |Cite
|
Sign up to set email alerts
|

The tetraspanin CD9 mediates lateral association of MHC class II molecules on the dendritic cell surface

Abstract: antigen presentation ͉ major histocompatibility complex class II ͉ B cell ͉ CD81 ͉ costimulatory molecules

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 47 publications
6
96
1
Order By: Relevance
“…MHC-II molecules loaded with specific antigenic peptides appear to be enriched in TEMs (30,47), and it has been suggested that TEMs might increase the chance of successful presentation of a limited pool of MHC-II molecules loaded with specific peptides. This would be in agreement with the observation that tetraspanins are constituents of IS (34).…”
Section: Discussionmentioning
confidence: 99%
“…MHC-II molecules loaded with specific antigenic peptides appear to be enriched in TEMs (30,47), and it has been suggested that TEMs might increase the chance of successful presentation of a limited pool of MHC-II molecules loaded with specific peptides. This would be in agreement with the observation that tetraspanins are constituents of IS (34).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps pMHCII uses the clathrinindependent carrier (GLIC)/GPI-AP-enriched early endosomal compartment (GEEC) pathway, an endocytosis route that is also used by lipid raft-associated molecules like GPI-linked proteins and cholera toxin B (Mayor and Pagano 2007;Howes et al 2010). Furthermore, tetraspanin-enriched microdomains have been implicated in clustering and routing of MHCII from the plasma membrane (Hammond et al 1998;Engering and Pieters 2001;Kropshofer et al 2002;Zilber et al 2005;Poloso et al 2006;Unternaehrer et al 2007). Tetraspanins belong to a family of proteins that span the membrane four times and are palmitoylated, a posttranslational modification that stimulates lateral partitioning into protein/lipid domains (Kovalenko et al 2004;Yáñez-Mó et al 2009).…”
Section: Trafficking Of Pmhciimentioning
confidence: 99%
“…CD9 is such a tetraspanin that could provide co-stimulation to naive T lymphocytes and was preferentially expressed on the human CD4 + CD45RA + naive T cell subset and involved in T cell activation [7,8]. And it was selectively expressed in DCs and necessary for the association of heterologous MHC-II and facilitated the formation of MHC-II multimers expected to enhance TCR stimulation by DCs [9].…”
Section: Introductionmentioning
confidence: 99%